Impact of Financial Constraints on Treatment Choices and Quality of Life Among Breast Cancer Patients - Reeta Singh Gaur, Pushpendra Kumar Shukla (South Eastern European Journal of Public Health, 2025)
Background Breast cancer is the most common cancer in women and a leading cause of death worldwide. Many patients in low-resource settings, such as India, struggle to access advanced therapies due to financial constraints. Chemotherapy remains a common treatment choice, despite its side effects, because it is more affordable compared to targeted therapies. This study examines the economic burden & impact on quality of life (QoL) for breast cancer patients undergoing chemotherapy & targeted therapy. Methods This study was conducted over six months, a multicenter study with 200 breast cancer patients. Data included patient demographics, clinical details, treatment type, side effects & both direct & indirect treatment costs. QoL was assessed using st&ard tools, the EORTC QLQ-C30 & QLQ BR-23. Statistical analyses, including correlations & t-tests, were used to identify relationships between therapy type, QoL & financial constraints. Results Out of 200 patients 73% received chemotherapy & 27% chose targeted therapy. Financial constraints were the main reason for selecting chemotherapy despite advice for targeted therapy (84.2%). Chemotherapy patients reported higher complications such as nausea/vomiting (69.9%) & hair loss (75.3%) compared to targeted therapy. Chemotherapy negatively affected QoL (r = -0.55, p = 0.013), while targeted therapy had a positive effect on QoL (r = 0.48, p = 0.021). Financial burden also strongly impacted QoL (r = -0.62, p < 0.001). Conclusion This study shows that financial issues play a major role in treatment decisions for breast cancer. Many patients choose chemotherapy due to its affordability, even though it reduces QoL & causes more side effects compared to targeted therapy. The findings highlight the need for affordable cancer treatments, better healthcare policies & financial support to improve outcomes & quality of life for breast cancer patients.